Cabling : the complete guide to copper and fiber-optic networking - Oliviero, Andrew, 1966- (Wiley Pub., 2009)
"With the growing demand for fiber optics in large-scale communications networks, network professionals need complete, up-to-the-minute information. The fourth edition of this popular guide provides you with the latest on copper and fiber-optic networking. It is particularly useful for those studying for the Fiber Optics Installer or Fiber Optics Technician certifications. Part I covers the basics of cabling, while Part II is devoted to in-depth information on fiber optics, allowing you to stay up to speed on all aspects of the field."--Resource description page